EFEKTIVITAS PELATIHAN MANAJEMEN AIR MINUM BERBASIS KOMPETENSI DALAM MENINGKATKAN PELAYANAN DI PERUMDAM LAWU TIRTA KABUPATEN MAGETAN - Tri Waryani; Eva Hany Fanida; Meirinawati; Trenda Aktiva Oktariyanda (Jurnal Riset Multidisiplin Edukasi, 2026)
Competency-based training is an important strategy for improving public service quality, particularly in regional water utility companies. At Perumdam Lawu Tirta, Magetan Regency, service challenges remain, including delays in handling water distribution disruptions, suboptimal employee responsiveness, and the limited implementation of training outcomes. This study aims to describe the effectiveness of competency-based drinking water management training in improving public services. A descriptive qualitative approach was employed using interviews, observations, and documentation. Training effectiveness was analyzed based on Noe's theory, which includes improvements in knowledge, skills, and work attitude. The findings indicate that the training has been effective in enhancing employees' knowledge, technical and customer service skills, and professional, disciplined, and responsive work attitudes. These competency improvements have contributed to better service quality through faster task completion, greater compliance with standard operating procedures, and improved responsiveness to customer needs.